2022
DOI: 10.1126/sciadv.add3914
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and structure of a clathrin-independent AP-1:Arf1 tubular membrane coat

Abstract: The adaptor protein (AP) complexes not only form the inner layer of clathrin coats but also have clathrin-independent roles in membrane traffic whose mechanisms are unknown. HIV-1 Nef hijacks AP-1 to sequester major histocompatibility complex class I (MHC-I), evading immune detection. We found that AP-1:Arf1:Nef:MHC-I forms a coat on tubulated membranes without clathrin and determined its structure. The coat assembles via Arf1 dimer interfaces. AP-1–positive tubules are enriched in cells upon clathrin knockdow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…AP-1 15 , 16 , 33 , AP-3 18 , 34 , and AP-4 35 have all been reported to be recruited to membranes through direct interaction with the small GTPase, Arf1. Through a multitude of structures and mutational analyses 26 , 27 , AP-1 has been shown to bind to Arf1 in two distinct locations — the γ and β1 subunits. Each interface interacts with Arf1 through the Switch I and II regions, explaining the GTP dependence of Arf1/AP-1 binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AP-1 15 , 16 , 33 , AP-3 18 , 34 , and AP-4 35 have all been reported to be recruited to membranes through direct interaction with the small GTPase, Arf1. Through a multitude of structures and mutational analyses 26 , 27 , AP-1 has been shown to bind to Arf1 in two distinct locations — the γ and β1 subunits. Each interface interacts with Arf1 through the Switch I and II regions, explaining the GTP dependence of Arf1/AP-1 binding.…”
Section: Resultsmentioning
confidence: 99%
“…The insight that AP-1 is natively closed 10 and AP-3 is natively open suggests that each complex has distinct pathways to forming vesicular and tubular coats. A recent report showed that AP-1 can polymerize on membrane tubules in an Arf1-dependent, clathrin-independent manner 26 , suggesting that AP-1 acts to deform membranes and sort cargo into tubular assemblies before budding into clathrin-coated structures. However, a similar understanding of AP-3 function is hampered by a lack of structural and mechanistic information.…”
mentioning
confidence: 99%
“…6D-E). Similarly, aside from its ability to induce membrane curvature, clathrin might be required for the clustering of AP-1 at sites of cargo exchange, as the lack of clathrin leads to diffused localization of AP-1 along tubular structures 55 . The presence of AP-1 and AP-3 nanodomains on ARF1 compartments involved in Tfn recycling (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ion-pair reversed-phase acetonitrile gradient HPLC was used to assay the nucleotide bound to VPS15 with a protocol adapted from ref. 35 . First, PI3KC3-C1 was denatured by heating in a heat block at 90 C for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%